Horizontal Spatial Metaphors for Morality: A Cross-Cultural Study of Han Chinese Students and Ethnic Minority Hui Students in China - Chen, Rui; Sai, Jiao; Zhu, Qi; Zhou, Renlai; Li, Peng; He, Shunchao (Frontiers in Psychology, 2018)
Metaphor is a bridge for understanding abstract concepts (the target domain) from concrete concepts (the source domain). This study, with 2 experiments, aimed to investigate the cultural differences of the horizontal spatial metaphors for morality between two groups of students: Han Chinese, the ethnic majority, and Hui Chinese, an ethnic minority in China. Experiment 1 adopted a spatial Stroop task. It showed that neither Hui nor Han students exhibited horizontal spatial metaphors for morality. Experiment 2 adopted a modified implicit association test (IAT) paradigm to enhance the association between the moral concepts and the horizontal spatial positions. In Experiment 2, we found horizontal spatial metaphors for morality in Hui students, but not in Han students. These results indicated that the differences of horizontal spatial metaphors between Hui and Han participants were influenced by the different cultures they live in. Moreover, this study also found that the association between the source domain and the target domain was an important factor for metaphor formations.